HOW IS THE BLUE ECONOMY IMPLEMENTED IN FISHERIES MANAGEMENT WITHIN THE RIAU ISLANDS? - Satrio Candra Nugroho; Endah Kurnia Lestari; Nandhito Figa Putra Teras; Aditya Ferdama Putra (Journal of Applied Economics in Developing Countries, 2026)
This study aims to examine fisheries management factors through a blue economy perspective. It is a quantitative study with an explanatory approach, using panel data regression as the analysis method with an observation period from 2020 to 2023 across seven districts in the Riau Islands. Data were obtained from Statistics Indonesia and the Ministry of Maritime Affairs and Fisheries. The results show that the marine resource sustainability index significantly increase the value of fishery production through a blue economy perspective. Theoretically, this study explains the Tragedy of the Commons Theory, by operationalizes the blue economy paradigm into measurable variables aligned with environmental, social, and economic dimensions which is relevant to the classical approach in natural resource economics, where fishery resources are considered public goods vulnerable to overexploitation for personal gain, ultimately harming everyone in the long run. The results provide empirical evidence that ecosystem-based management remains central to sustaining fisheries output in archipelagic regions. The study contributes to applied development economics by offering a provincial-level panel analysis of fisheries sustainability within a small-island and archipelagic context.